A reassessment of global bioenergy potential in 2050. Issue 2 (8th February 2014) - Searle, Stephanie; Malins, Chris
Abstract Many climate change mitigation strategies rely on strong projected growth in biomass energy, supported by literature estimating high future bioenergy potential. However, expectations to 2050 are highly divergent. Examining the most widely cited studies finds that some assumptions in these models are inconsistent with the best available evidence. By identifying literature‐supported, up‐to‐date assumptions for parameters including crop yields, land availability, and costs, we revise upper‐end estimates of potential biomass availability from dedicated energy crops. Even allowing for the conversion of virtually all 'unused' grassland and savannah, we find that the maximum plausible limit to sustainable energy crop production in 2050 would be 40–110 EJ yr−1. Combined with forestry, crop residues, and wastes, the maximum limit to long‐term total biomass availability is 60–120 EJ yr−1 in primary energy. After accounting for current trends in bioenergy allocation and conversion losses, we estimate maximum potentials of 10–20 EJ yr−1 of biofuel, 20–40 EJ yr−1 of electricity, and 10–30 EJ yr−1 of heating in 2050. These findings suggest that many technical projections and aspirational goals for future bioenergy use could be difficult or impossible to achieve sustainably.